Analysis of Eating Patterns and Pregnancy Distance with the Incidence of Anemia in Pregnant Women in Macanan Village, Loceret Public Health Center, Nganjuk Regency - Nita Pranita Yuniarwati; Betty Fitriasari (PT. Griya Eka Sejahtera, 2022)
Background: Anemia is an event that is often experienced by pregnant women, the cause of anemia is more due to inappropriate eating patterns and risky pregnancy intervals. This study aimed to analyze the relationship between diet and pregnancy spacing with the incidence of anemia in pregnant women.Methods: This type of research uses a cross sectional approach , the instruments used are observation sheets and questionnaire sheets, the population in this study is pregnant women who experience anemia, namely 25 people with a sample of 20 respondents using cluster random sampling technique, this study uses Chi square test analysis.Results: This study showed that results of bivariate analysis with chi square test with a significant value of 0.000 (p < 0.05), which means that there is a relationship between eating patterns and pregnancy spacing with the incidence of anemia in pregnant women.Conclusion: There is a relationship because the occurrence of anemia is generally caused by an unbalanced diet. This is due to the low nutritional awareness of the community, especially pregnant women, while repeated pregnancies with a short time span will cause iron reserves in the mother's body to have not been fully recovered and then again depleted for the needs of the fetus being conceived